Whitelists as blacklists: The use of external lists when evaluating scientific journals - Lavik, Gry Ane (Septentrio Conference Series, 2017)
Watch the VIDEO here. NSD – Norwegian Centre for Research Data operates the Norwegian Register for Scientific Journals, Series and Publishers on behalf of the University and Higher Education Council. The publishing arena for researchers is changing. Yet every researcher is responsible for publishing in channels that are serious and have a professional impact. At NSD we experience that there is a need for advice about where to publish and about how to recognize quality in new international publication channels. Much of the need for advice stems from the increase of new open access channels and the pressure towards publishing in these channels. The somewhat notorious Beall’s list closed down last year. All though controversial, this list was a useful tool to become aware of channels to check more closely. It also provided a useful checklist to use when evaluating OA-channels. So what to do with no such blacklist operating?* At the Norwegian register, we have come to believe that multiple whitelists can work in much the same way or even better than a blacklist. A simple explanation for this is that if a journal is not featuring on any whitelist, this says something about the quality of the journal in much the same way a blacklist does by including it. But there are fallacies and problems to be aware of when using this approach. The aim of this presentation is to problematize advantages and disadvantages connected to the use of whitelists as a form of quality control. To this end a description of how whitelists are used when evaluating channels for inclusion in the Norwegian register will form the basis for the presentation. The term “whitelist” is here used in broad sense, denoting a list that only includes journals after making some sort of positive judgement about the quality of the journal while leaving out journals considered of poor quality. The Norwegian register has recently entered a Nordic collaboration which gives access to compare with the Finnish and the Danish national lists of authorized research publication channels. A closer collaboration with Directory of Open Access Journals - DOAJ was also formally in place earlier this year. A description of the Nordic list project and some thoughts on the expected outcome of the collaboration will be part of the presentation.